Materials characterization of potassium sodium niobate based tellurite glass-ceramics - Ploypailin Yongsiri (2018)
In this research, materials characterization of transparent glass-ceramics containing ferroelectric potassium sodium niobate (K 0.5 Na 0.5 )NbO 3 (KNN) crystals in a tellurite glass system were studied. The samples were prepared via an incorporation method. Glass-ceramics containing KNN crystals were successfully fabricated by mixing KNN calcined powder with TeO 2 of about 70 and 80 mol% and melting at 800°C for 15 min in a platinum crucible. The prepared glasses were then subjected to heat treatment at 350-550°C. The optical properties of the samples were characterized by UV-Vis-NIR and ellipsometer. It was found that heat treatment temperature had significantly affected the optical properties. XRD patterns of the glass-ceramics revealed an amorphous-like structure with different degrees of crystallinity. SEM results confirmed the XRD data, where the degree of crystallinity increased with increasing heat treatment temperature. Copyright © Taylor & Francis Group, LLC.